Assessment of the tensile behaviour of cast-in headed anchors with void formers in early age concrete. (24th January 2022) - Obayes, Osamah; Gad, Emad; Lee, Jessey; Pokharel, Tilak; Abdouka, Kamiran
Highlights: Concrete cone failure and pull-out failure of anchors with void formers. Pull-out failure occur for anchors in early age concrete prior to concrete cone failure. CC-method equation can be used for anchors in early age concrete. 3D Finite element analysis of anchors in early age concrete. A new prediction formula for pull-out failure is proposed. Abstract: This study investigates the tensile behaviour of cast-in headed anchors installed with void formers in early age concrete. Behaviour of anchors was addressed by three approaches; detailed assessment of concrete material properties; experimental testing of a total of 72 anchors in 4 different concrete mixes; and finite element analysis to expand on the experimental results. The study confirmed that pull-out failure can take place prior to concrete cone failure for anchors with void formers in early age concrete, contradicting what is predicted by models in literature. Results obtained from this study showed that when assessing pull-out failure for anchors with void formers, the embedment depth considered should be taken as the distance from the anchor foot to the bottom of the void, while for concrete cone failure it is taken from the anchor foot to the concrete surface. Further, this study confirmed the suitability of CC-method for anchors installed in early age concrete and proposed a modified model for predicting pull-out capacity of anchors with shallow embedment depth (<70 mm).